Impacts of Digital Marketing on the Pharmacies Community in Saudi Arabia and Determining the Future Model of the Industry: A Cross-Sectional Questionnaire-based Study - Alyahya, Mansour; Dhruvakumar, Sneha; Siddegowda, Shekar Hosahalli; Sreeharsha, Nagaraja (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Pharmaceutical and telemedicine industries are now finding ways in the Kingdom of Saudi Arabia by adopting innovative and successful business models along with groundbreaking strategies using digital online platforms particularly after the COVID-19 pandemic. Methods: The present study analyzes the impacts and frequencies of digital marketing technology usage among pharmacies and customers. A crosssection study was carried out using a non-repeated random sampling technique and a standardized questionnaire survey was conducted employing online telephone interviews. Binomial, Chi-square, multinomial logistic regression and the multivariate statistics were applied on data sets to determine the comparison and relationship between variables and their categories. Results: These study findings revealed that customers used the web services tool of pharmaceutical companies significantly (p<0.05) more than other digital marketing or social media platforms. Approximately, 36 pharmacies agreed out of 51 to the fact that webinars are effective, efficient and resourceful for online engagement with all shareholders regarding the product. Conclusion: Most respondents recognized that social media chats are to be more operative and ferocious in terms of marketing communications.
Keywords: Digital Marketing; Pharmacy; Pandemic; Digitalization; Social Media